Development and testing of a greenhouse assay for screening potato germplasm for susceptibility to Spongospora subterranea f. sp. subterranea (powdery scab) - Houser, Andrew J., author; Davidson, Robert D., advisor; Wallner, Stephen, committee member; Schwartz, Howard, committee member (Colorado State University. Libraries, 2008)
Potato resistance to powdery scab, caused by the protist Spongospora subterranea f. sp. subterranea (S.s.s.), has become extremely important in recent years due to the increased damage caused by this disease. Variable field conditions and the environmental sensitivity of the S.s.s. infection process in naturally infested fields have created difficulties in consistently evaluating potato germplasm resistance. A greenhouse assay for evaluating potato germplasm resistance which is consistent and compatible with field results was developed. Two soil types, three inoculum levels, two inoculum sources and two soil moisture regimes were evaluated in a greenhouse for powdery scab severity using four potato cultivars. Soil temperature was maintained at an ideal range for powdery scab development as reported in current literature. Greenhouse results were then compared with three years of fi eld data collected from field trials conducted in the San Luis Valley (SLV). Cultivars were evaluated for root galling, tuber lesion incidence, and severity. Soil with 50% sand, an inoculum level of one sporeball per gram of soil , and relatively high soil moisture (0-10 chars) had the most consistent symptom expression when compared with field results . This combination of factors was then tested m a greenhouse using fourteen potato cultivars which varied in levels of powdery scab susceptibility. A relative ranking system was also developed to compare greenhouse results with known SLY field results. Results demonstrated that a greenhouse assay can be used successfully for screening advanced potato germplasm for susceptibility to powdery scab.
Covers not scanned.
Keywords: Potatoes -- Disease and pest resistance; Potatoes -- Germplasm resources; Powdery scab